2011
DOI: 10.1088/0004-637x/731/1/41
|View full text |Cite
|
Sign up to set email alerts
|

Maximally Star-Forming Galactic Disks. I. Starburst Regulation via Feedback-Driven Turbulence

Abstract: Star formation rates in the centers of disk galaxies often vastly exceed those at larger radii, whether measured by the surface density of star formation Σ SFR , by the star formation rate per unit gas mass, Σ SFR /Σ, or even by total output. In this paper, we investigate the idea that central starbursts are selfregulated systems, in which the momentum flux injected to the interstellar medium (ISM) by star formation balances the gravitational force confining the ISM gas in the disk. For most starbursts, supern… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

44
488
2
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 346 publications
(539 citation statements)
references
References 82 publications
44
488
2
1
Order By: Relevance
“…The range of X CO values for high-z SMGs ranges from lower than to higher than the typical z ∼ 0 ULIRG value, and provides some evidence that the X-factor is not strictly bimodal. Moreover, Magnelli et al (2012) find an inverse relationship between the conversion factor and and dust temperature, which is consistent with the empirical inverse powerlaw correlation between X CO and gas surface density uncovered by Tacconi et al (2008) and Ostriker & Shetty (2011). Turning toward more 'normal' disk galaxies at high-z, Daddi et al (2010b) utilize dynamical arguments to infer α CO = 3.6±0.8 M pc −2 (K km s −1 ) −1 (i.e.…”
Section: Deriving H 2 Gas Masses From High-redshift Galaxiessupporting
confidence: 75%
See 4 more Smart Citations
“…The range of X CO values for high-z SMGs ranges from lower than to higher than the typical z ∼ 0 ULIRG value, and provides some evidence that the X-factor is not strictly bimodal. Moreover, Magnelli et al (2012) find an inverse relationship between the conversion factor and and dust temperature, which is consistent with the empirical inverse powerlaw correlation between X CO and gas surface density uncovered by Tacconi et al (2008) and Ostriker & Shetty (2011). Turning toward more 'normal' disk galaxies at high-z, Daddi et al (2010b) utilize dynamical arguments to infer α CO = 3.6±0.8 M pc −2 (K km s −1 ) −1 (i.e.…”
Section: Deriving H 2 Gas Masses From High-redshift Galaxiessupporting
confidence: 75%
“…These authors found that at high surface densities, one might expect the X-factor to drop, similar to the empirical findings of Ostriker & Shetty (2011). Narayanan et al (2011b) and Narayanan et al (2012a) coupled 3D non-local thermodynamic equilibrium (LTE) radiative transfer calculations and dust radiative transfer simulations with smoothed particle hydrodynamic (SPH) models of disk galaxies and galaxy mergers to derive a functional form for the CO-H 2 conversion factor across a variety of environments.…”
Section: Deriving H 2 Gas Masses From High-redshift Galaxiessupporting
confidence: 55%
See 3 more Smart Citations